Racial Differences in Neighborhood Perceptions and their Influences on Physical Activity among Urban Older Women - Wenjun Li; Elizabeth Procter-Gray; Gretchen A. Youssef; Scott E. Crouter; Jie Cheng; Kristen Brown; Linda Churchill; Anthony Clarke; Judith K. Ockene; Michelle F. Magee (AIMS Press, 2017)
Background: Proper levels of physical activity (PA) are important to healthy aging. Little is known about racial differences in influences of neighborhood perceptions (NP) on PA and use of neighborhood resources among community-dwelling older women. Materials and methods: In 2014 and 2015, 49 white and 44 black women of age 65 and older living in Washington, DC were queried about their PA, NP, use of neighborhood resources and sociodemographic characteristics. They wore an accelerometer and a Global Positioning System device concurrently for 7 consecutive days. Data were analyzed by race. Results: Compared to Whites, Blacks had lower NP scores (71% positive vs. 77%, p = 0.01), lower mean daily step counts (mean (SD): 3256 (1918) vs. 5457 (2989), p < 0.001), and lower frequencies of all exercise activities combined (19.7 (8.7) vs. 25.2 (11.8) per week, p = 0.01). For both Whites and Blacks, better NPs were associated with more frequent PA both at (p = 0.05) and away from home (p = 0.01). However, better NPs were associated with higher frequencies of exercise activities, moderate-to-high intensity activities, and utilitarian walking for Whites but not Blacks (p < 0.05 for race-perception interaction terms). Conclusions: In an urban setting, older Black women were more likely than older White women to have poor NPs, less PA, and weaker or no association of positive NPs with higher levels of certain PAs. Such substantial racial differences warrant further investigation and consideration in health promotion programs.